NEAR INFRARED IMAGING FOR ANGIOGRAPHY IN DIABETIC PATIENTS WITH PERIPHERAL ARTERY DISEASE - Z. N. Abdul`vapova; P. V. Grachev; E. V. Artemova; G. R. Galstyan; O. N. Bondarenko; A. M. Gorbacheva; K. G. Lin`kov; V. B. Loschenov (Biomedical Photonics)
The results of evaluation of the soft tissue perfusion of the foot in patients with diabetes and critical lower limb ischemia (CLI) via fluorescence angiography (FAG) in the near-infrared range are represented in the article. The study included 4 diabetic patients with CLI. All patients underwent lower-limb balloon percutaneous transluminal angioplasty. To evaluate the soft tissue perfusion of the foot via FAG the following parameters have been used: T0m - time to reach maximum for fluorescence intensity after intravenous administration of Indocyanine green; TIm- time of onset of maximum fluorescence intensity after its appearance in the area of interest; Im - the level of the maximum fluorescence intensity. The region of interest was the skin around the wound of the foot. The median FAG parameters in the region of interest on the foot were as follows: prior to surgery T0m = 164 sec (148–181), TIm = 48 sec (38–56); after surgery: T0m = 80 sec (69–92); TIm = 27 sec (20–39); (p <0,05). No adverse reactions were registered in the study. Despite the small sample we were able to achieve statistical significance in the difference between the parameters prior to and after surgery. Further prospective studies with extended samples of patients are needed.